Rapid assessment of lichen diversity in Baliem Valley, Jayawijaya, Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Suharno, Chrystomo LY, Sujarta P, Tanjung RHR. 2020. Rapid assessment of lichen diversity in Baliem Valley, Jayawijaya, Papua, Indonesia. Biodiversitas 21: 2403-2409. Lichen is a form of mutualistic symbiosis between phycobiont and mycobiont. Lichens play an important role in environment, either to maintain the biological diversity and the function of ecosystems. This study is aimed to determine the diversity of species of lichens in the Baliem Valley region, Jayawijaya, Papua. The method used was explorative surveys in several villages in Jayawijaya District. Species identification was based on morphological characteristics. The results showed that there were 37 species of lichen belong to 24 genera and 11 families on several habitats on altitude ranging from 1655 to 2179 m asl with temperatures between 18-26°C. The dominant species were from the families of Parmeliaceae, Cladoniaceae, and Teloschistaceae. The results indicate that the Baliem Valley region rich in lichen diversity and the existence of particular lichen species suggests that the region has healthy environmental conditions. This study provides new information on the existence of lichen diversity in Papua.
Keywords: Baliem valley, lichens, symbiosis, Jayawijaya